STUDI LITERATUR TENTANG PENGARUH EDUKASI GIZI BERBASIS TEKNOLOGI DIGITAL TERHADAP PENGETAHUAN GIZI PADA REMAJA - cecep abdul cholik; Muhamad Ikhsan Prawira Negara; Dwi Mitha Oktaviani (Jurnal Fakultas Teknik Kuningan, 2024)
This study outlines how nutrition education based on digital technology serves as a strategy to enhance nutritional understanding among adolescents. The approach employed is literature review. The conclusion drawn from this research is that providing nutrition education through digital technology successfully improves nutritional knowledge among adolescents. However, there is no certainty regarding the presence of a significant relationship between interventions in two groups, namely the intervention group and the control group. This conclusion is supported by findings from previous research conducted by other researchers.